2019
DOI: 10.3389/fphys.2019.00201
|View full text |Cite
|
Sign up to set email alerts
|

Control and Regulation of Substrate Selection in Cytoplasmic and Mitochondrial Catabolic Networks. A Systems Biology Analysis

Abstract: Appropriate substrate selection between fats and glucose is associated with the success of interventions that maintain health such as exercise or caloric restriction, or with the severity of diseases such as diabetes or other metabolic disorders. Although the interaction and mutual inhibition between glucose and fatty-acids (FAs) catabolism has been studied for decades, a quantitative and integrated understanding of the control and regulation of substrate selection through central catabolic pathways is lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…The finding indicates that the need for higher concentration of DiMAL may be caused by factors other than protein content and complex II activity, e.g. metabolic rate control or substrate selection beyond the mechanisms traditionally claimed to explain the glucose-fatty-acid cycle 37 . Using dosages optimized to non-diabetic trabeculae, we found no protection by DiMAL in patients with diabetes.…”
Section: Discussionmentioning
confidence: 89%
“…The finding indicates that the need for higher concentration of DiMAL may be caused by factors other than protein content and complex II activity, e.g. metabolic rate control or substrate selection beyond the mechanisms traditionally claimed to explain the glucose-fatty-acid cycle 37 . Using dosages optimized to non-diabetic trabeculae, we found no protection by DiMAL in patients with diabetes.…”
Section: Discussionmentioning
confidence: 89%
“…Heart and kidneys have different energy demands, and hence, their mitochondrial OxPhos capacities and efficiencies are expected to be different [ 80 , 81 ]. However, integrated quantitative studies have not been undertaken to shed light on the reasons for the differences in the OxPhos capacities and efficiencies of these organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that T‐cell aging modifies mitochondrial function and glycolysis. Since changes in the metabolic pathway may also affect the selection of fuel by mitochondria, (Cortassa et al, 2019), we next dissected the energy source utilized by mitochondria in young and old naïve CD4 + T cells using a mito fuel assay.…”
Section: Resultsmentioning
confidence: 99%